Design and preliminary evaluation of an immersive 3D stereoscopic simulation game for historical education: the Hindenburg disaster - Khairil Khusnin, Khairil Nazrel; Muhamad Rashidi, Muhammad Fayyadh; Zainal Azmi, Nurazlin (IIUM Press, 2026)
History education often relies on static text and images, offering limited opportunities for experiential learning about complex historical events. This study addresses this gap by designing and examining an immersive 3D stereoscopic simulation game centered on the 1937 Hindenburg disaster. The objectives were: (i) to model a historically informed 3D replica of the Hindenburg environment, (ii) to develop an interactive gameplay experience that situates players within the unfolding event, and (iii) to conduct a pilot evaluation of usability and perceived educational value. The game was developed using Blender for asset creation and Unreal Engine 5 for implementation, following an iterative pipeline of pre-production, production, and post-production. A toggleable stereoscopic mode was integrated to enhance depth perception and immersion. The pilot evaluation was conducted with four participants using functional testing and user-acceptance feedback. Results indicated that users found the application easy to navigate, immersive, and supportive of understanding the sequence and context of the disaster, while also identifying areas for improvement such as clearer guidance and expanded interaction features. These findings provide preliminary evidence that stereoscopic serious games can serve as promising supplementary tools for historical learning and motivate future refinement and larger-scale empirical evaluation